RADI-18. STEREOTACTIC RADIOSURGERY OR FRACTIONATED STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASES FROM SMALL CELL LUNG CANCER. (12th August 2019) - Thomas, Evan; Travis, Roman; Boggs, D Hunter; Marcrom, Sam; Markert, James; Spencer, Sharon; Riley, Kristen; Strickler, Scott; Bredel, Markus; Willey, Christopher; Guthrie, Bart; Fiveash, John
Abstract: BACKGROUND: Current standard of care (SOC) management of the brain differs between non-small cell lung cancer (NSCLC) & small cell lung cancer (SCLC). For SCLC, WBRT is considered SOC, even for solitary metastasis. In the setting of no-known metastases, prophylactic cranial irradiation (PCI) is considered SOC. SRS is occasionally utilized in SCLC, e.g. in setting of limited metastasis after WBRT/PCI, or limited metastasis after excellent systemic response to extracranial therapy, or if patient declines WBRT. In this study, we sought to understand more about the nature and outcomes of patients with SCLC who received intracranial SRS at our institution. METHODS: We reviewed radiosurgery treatments from 2005 thru 2019 for patients with SCLC who received SRS. Variables included were: time interval between diagnosis/SRS and death, prior WBRT/ PCI, number of targets, performance status, modality (GK or linac), prior surgery, and available follow-up. RESULTS: We identified 92 SRS treatments among 74 patients. 30 received upfront SRS, the remainder as post-WBRT/PCI salvage. Median survival after initial diagnosis was 22.0 months (min = 6.6, max 55.4). Median survival after first SRS was 6.1 months (min = 0.5, max = 40.4). Median recorded KPS was 75.6. Mean number of mets treated was 3.4 (min = 1, max = 12). Prescription dose range was 12 to 20Gy in single fraction, and 25 to 30Gy in five fraction treatment. 53 treatments were performed on Gamma Knife, 37 with linear accelerator. Four patients were treated post-operatively, one patient was treated pre-operatively. CONCLUSIONS: Survival in our cohort of SCLC patients receiving intracranial SRS compared favorably with historical SCLC controls (8-13mo after dx). Future work will seek to clarify whether there is a difference in brain metastasis velocity between patients treated with upfront PCI/WBRT or SRS, and also seek to address the minimum necessary dose to control SCLC metastases.